Zestig jaar toneelliteratuur in België - Lilar, Suzanne; Gijsen, Marnix (Antwerpen : De Sikkel, 1951)
Bibliotheek Camille Huysmans
Dedicator: Lilar, Suzanne, dedicatee: Huysmans, Camille
Nederlands
Monografie
Keywords: toneel